Praktik Sosial Pengasuhan Anak Terinfeksi HIV dan AIDS dalam Keluarga di Kota Padang : Studi EnamKeluarga dengan Anak Terinfeksi HIV/AIDS - Muharman Muharman; Jendrius Jendrius; Indradin Indradin (Institut Agama Islam Negeri (IAIN) Curup, 2019)
Child Protection Regulation in Indonesia believes the family as the main support system for children with various problems including HIV / AIDS. This policy is based on the view that places the family as the main institution of child protection. Because people with HIV / AIDS are still stigmatized, this is a family challenge to provide care for children with HIV / AIDS. The challenge is between telling the child's HIV / AIDS status to get broader support in care, by avoiding stigmatization. In this dilemma the questions that will be answered in this article are what are parents doing in caring for children infected with HIV / AIDS, how to avoid stigma from the social environment, what social structures are able to block and hinder the quality of care and care. This research uses a qualitative method based on case studies of 6 families with children infected with HIV / AIDS through the mother to child transmission pathway. This article shows that HIV / AIDS infection through mother-to-child transmission can also describe negative parental risk behaviors according to community moral standards. Parents try to hide the infection status of their children from other family members by moving from one place to another. This strategy of avoiding stigmatization does not affect health care and treatment even if their status is known by existing health care units. However, there is anxiety that their child's family will not get their rights to education, social relations and other social support needed for growth and development, if their HIV / AIDS status is opened. Thus the results of this study demanded the reengagement of the family as the main support system for the care and care of children with HIV / AIDS. The limitation of this study is that the children studied are infected from mother to child transmission, so children who are transmitted in other ways have not been revealed by this study.